2017
DOI: 10.2147/dmso.s135064
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia and associated factors among diabetic patients attending Durame General Hospital in Southern Nations, Nationalities, and People’s Region

Abstract: BackgroundDiabetes mellitus is a group of metabolic disorders that are caused by deficiency in insulin secretion or the decreased ability of insulin to act effectively on target tissues, particularly muscle, liver, and fat. As a result of insulin resistance in the target tissues, particularly in the adipocytes, free fatty acid flux is increased, leading to increased lipid synthesis in hepatocytes, which is responsible for diabetic dyslipidemia.ObjectiveThe objective of this study was to determine the prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
50
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(88 citation statements)
references
References 10 publications
27
50
11
Order By: Relevance
“…The finding was comparable with the prevalence reported by Abdel-Aal et al (2008), which was 90%. However, the rate is much higher when compared with the study conducted in other part of Ethiopia (Bekele et al, 2017) where the prevalence of dyslipidemia was 65.6%. We found that the prevalence of abnormal lipid profiles of low HDL-c, high LDL-c, TG and TC were 60.8, 14.3, 70.4 and 32.8%, respectively.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…The finding was comparable with the prevalence reported by Abdel-Aal et al (2008), which was 90%. However, the rate is much higher when compared with the study conducted in other part of Ethiopia (Bekele et al, 2017) where the prevalence of dyslipidemia was 65.6%. We found that the prevalence of abnormal lipid profiles of low HDL-c, high LDL-c, TG and TC were 60.8, 14.3, 70.4 and 32.8%, respectively.…”
Section: Discussioncontrasting
confidence: 61%
“…The rate of low HDL-c, raised LDL-c, hypertriglyceridemia and hypercholesterolemia was lower than the finding reported from Jordan (Abdel-Aal et al, 2008) where 83.9, 91.5, 77.2, and 83.1% were the prevalence of low HDL-c, raised LDL-c, TC and TG, respectively. Conversely, lower rate of abnormal lipid profiles was reported from other similar region of South Ethiopia except LDL-c (Bekele et al, 2017). The variability may be attributed to the variations in individual's life style, geographical location, the rate of physical exercise performance.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In regard to obesity condition factor measured by BMI, the current study demonstrated a risk effect on dyslipidemia, similar to the findings from previous studies [7, 28]. Accumulating evidence indicate that a state of chronic inflammation play a crucial role in the pathogenesis of obesity-related metabolic dysfunction [2931].…”
Section: Discussionsupporting
confidence: 89%